Menthol Preference Among Smokers: Association With TRPA1 Variants - Uhl, George R. (Oxford University Press, 2011)
INTRODUCTION: Preference for smoking menthol cigarettes differs from individual to individual and population to population in ways that may provide higher levels of nicotine intake and contribute to smoking’s morbidity and mortality. Menthol acts at sites that include the transient receptor potential (TRP) A1 channel that is expressed by nociceptors in the lung and airways, suggesting that individual and population differences in TRPA1 sequences might contribute to observed differences in menthol preference among smokers. METHODS: We have thus sought association between menthol preference and common variants in the TRPA1 gene in heavier and lighter European-American smokers. Smokers were recruited for studies of smoking cessation in North Carolina and of substance abuse genetics in Maryland. RESULTS: A common TRPA1 haplotype is defined by 1 missense and 10 intronic single nucleotide polymorphisms that display significant (.006 < p < .05; χ(2)) association with preference for mentholated cigarettes in heavy smokers (odds ratio ca. 1.3). There are smaller trends in the same direction in lighter smokers. CONCLUSIONS: This TRPA1 haplotype provides a novel biological basis for individual differences in menthol preference and possibly for actions of other agents that act at TRPA1.